Haematological Effects of Methanol and n-Hexane Seed Extracts of Hunteria umbellata (abeere) on Alloxan Induced Diabetic Wistar Rats - Obia, Chika; Nwuke, P Chinedu; Okereke, Goodluck Obioma (British Journal of Healthcare and Medical Research, 2023)
There is growing research studies in identifying local medicinal plants with potentials in replacing the orthodox medicines and synthetic drugs that are now expensive, less effective with side effects when used in treatments of chronic diseases like diabetes mellitus. The chemical compositions, and effects of Methanol and n-Hexane extracts of Hunteria umbellata (HU) seeds (folkloric remedies for diabetes, obesity, anaemia etc.) on haematological parameters of alloxan induced diabetic wistar rats, were investigated. Thirty albino rats were divided into six groups- (1) Diabetic rats without treatment (Negative control); (2) Diabetic rats, treated with glibenclamide; (3) Diabetic rats treated with 250mg/kg body weight of methanol extract of HU seeds;(4) Diabetic rats treated with 500mg/kg body weight of methanol extract of HU seeds; (5) Diabetic rats treated with 250mg/kg body weight of n-hexane extract of HU seeds; (6) Diabetic rats treated with 500mg/kg body weight of n-hexane extract of HU seeds. Treatments of the induced diabetic rodents lasted for 14 days before they were sacrificed and blood was collected for biochemical evaluation. From the results, significant (P≤ 0.05) high white blood cells, platelets and mean corpuscular volume were observed in group 2. Reducing sugars (in high amounts), flavonoids, tannin, alkaloids, saponins and 14 important compounds were found present in the HU seed extracts. The acute toxicity study of the extracts showed no death at doses of up to 500 mg/kg body weight after 24 h and for 7 days of observation. Treatments with glibenclamide, and extracts of HU seeds at various doses significantly increased (P<0.05) the red blood cells (RBC), packed cell volume and hemoglobin but significantly (P<0.05) reduced the white blood cells and platelets of the Haematological parameters. Thus, Methanol and n-Hexane extracts of HU seeds possess anti-hyperglycemic effects on the haematology due to their high contents of phytochemicals.